CNC LATHE: evolution, characteristics and importance for machining - Oliveira da Silva, Sandro; Ramalho Reis Filho, Ramilio Ramalho Reis Filho (Revista Interface Tecnológica, 2022)
This article consists of a literature review, which aims to present the CNC lathe (Computer numerical control) its evolution, characteristics and implications in the machining sector. Throughout the work will be discussed, about the creation of the same that in the beginning was totally rudimentary, and the operations were based on the skill of the turner. As humanity evolves in terms of technology and the need to adapt to the new reality facing the globalized world, the lathe with computerized numerical control appears, an important tool in the manufacturing process in the machining sector, due to the high precision with which it performs the turning. and sizing of complex parts with lower incidence of errors, loss of time and money throughout the process, meeting deadlines and product quality according to customer requirements. Such factors contribute for the machining sector, an important activity, considered one of the most popular manufacturing processes in the world, to become competitive through competition. Overall, research has proven the efficiency of the CNC lathe, but as a future proposal, there is greater interest in new publications on this subject. This article does not intend to exhaust the subject, but that it can help those who are interested in the subject.
Keywords: CNC lathe; Evolution; Machining